Development of a Flipbook-Based Digital Pocketbook on Environmental Pollution Material on the Critical and Creative Thinking Skills of Class VII Students at SMPN 1 Sojol Utara - Novirianti Novirianti; Achmad Ramadhan; Masrianih Masrianih (Publikasi Indonesia, 2024)
This study aims to develop and see the effectiveness of flipbook-based digital pocketbooks on environmental pollution material on the critical and creative thinking skills of grade VII students at SMPN 1 Sojol Utara. The method used in this research is research and development (Research and Development) with 4D instructional design. This research was conducted on grade VII students at SMPN 1 Sojol Utara totaling 40 students. The results of this study showed that: (1) The flipbook-based digital pocket book developed obtained a percentage of 86.96% of the very valid category and for media practicality obtained a percentage of 80% of the practical category for use in science learning, critical thinking skills obtained a value of 70.83% in the critical thinking category (2) The ability to think creatively obtained a score of 84.37% with the category of creative thinking (3) The effectiveness of the book The flipbook-based digital pocket developed is very effective in improving students' critical thinking skills with an effect size value of 1.95 very large categories, (4) The effectiveness of the flipbook-based digital pocketbook developed is very effective in improving students' creative thinking skills with an effect size valueThe 1.95 categories are huge. Based on the results of the development that has been carried out, flipbook-based digital pocketbooks can be a learning medium that can improve students' critical and creative thinking skills in science learning.